Analysing the impact of a renewable hydrogen quota on the European electricity and natural gas markets - David Schlund; Max Schönfisch (Institute of Energy Economics at the University of Cologne (EWI), 2021)
We perform a model-based analysis of the impact of a renewable hydrogen quota on EU gas and electricity markets. By comparing a scenario in which a renewable hydrogen quota with tradable certificates is imposed on final gas consumption in the sectors of the economy outside the EU ETS with a reference scenario without a quota, we assess price, quantity and welfare effects. Our model simulations show that the hydrogen quota leads to a significant expansion in renewable energy sources (RES) capacity to produce renewable hydrogen and synthetic methane with Power-to-Gas (PtG) technologies. On the electricity market, the price increases substantially, rising by up to 12% - mostly due to increasing emission allowance prices - leading to a higher surplus for power producers. The quota's primary beneficiaries in the power sector are renewable energy producers. On the gas market, the quota leads to a small decrease in prices (by a maximum of -3%) and gas producer surpluses. Quota obliged gas consumers, mainly households, commercial and small industrial consumers, carry the largest part of the burden associated with the obligation. Overall, the quota leads to the redistribution of welfare from these consumers to RES and PtG producers and a significant decline in total welfare.
Keywords: C61; Q41; Q42; Q48; 330; Hydrogen; power-to-gas; quota obligation; renewable energy support